2021
DOI: 10.3390/cancers13225815
|View full text |Cite
|
Sign up to set email alerts
|

A Polygenic Risk Score Predicts Incident Prostate Cancer Risk in Older Men but Does Not Select for Clinically Significant Disease

Abstract: Despite the high prevalence of prostate cancer in older men, the predictive value of a polygenic risk score (PRS) remains uncertain in men aged ≥70 years. We used a 6.6 million-variant PRS to predict the risk of incident prostate cancer in a prospective study of 5701 men of European descent aged ≥70 years (mean age 75 years) enrolled in the ASPirin in Reducing Events in the Elderly (ASPREE) clinical trial. The study endpoint was prostate cancer, including metastatic or non-metastatic disease, confirmed by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Although polygenic risk scores have been associated with prevalent and incident disease, 1 prior studies have shown that they do not improve risk prediction for aggressive prostate cancers with the potential to be fatal. 2,3 In this study, we compared the polygenic risk score (PRS 269 ) as defined by Conti et al 4 to the Prostate Biopsy Collaborative Group risk calculator, 5 a clinical tool that computes the probabilities of finding (1) any cancer and (2) high-grade (GG ≥2) cancer on biopsy results in men undergoing a first prostate biopsy.…”
Section: A Polygenic Risk Score For Prostate Cancer Risk Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although polygenic risk scores have been associated with prevalent and incident disease, 1 prior studies have shown that they do not improve risk prediction for aggressive prostate cancers with the potential to be fatal. 2,3 In this study, we compared the polygenic risk score (PRS 269 ) as defined by Conti et al 4 to the Prostate Biopsy Collaborative Group risk calculator, 5 a clinical tool that computes the probabilities of finding (1) any cancer and (2) high-grade (GG ≥2) cancer on biopsy results in men undergoing a first prostate biopsy.…”
Section: A Polygenic Risk Score For Prostate Cancer Risk Predictionmentioning
confidence: 99%
“…It is both notable and reassuring that the inclusion of a modest amount of men with African ancestry, East Asian ancestry, and Hispanic ethnicity in building the PRS 2 resulted in a score that appears to perform as well in men with European and African ancestry in this independent replication. 1 Further increasing representation of non-European participants in these genetic studies and more sophisticated algorithms for including multiancestry data 3 will help ensure that PRS will be valid and useful among all populations.…”
Section: Supplemental Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Hormonal therapy, radiotherapy, chemotherapy, and surgical treatment should be chosen according to the stage of the illness ( 8 ). The incidence of CS-PCa is higher in older men and men with no family history ( 9 ). Early detection of CS-PCa is of profound significance for the effective treatment of patients.…”
Section: Introductionmentioning
confidence: 99%